Membrane based cross flow heat and mass exchanger for dehumidification - Ng, Wei Kiat (2015)
The report describes the comparison of a newly designed membrane-based cross flow heat and mass exchanger for dehumidification against that of an existing industrial membrane system. In recent years, huge amounts of funding are pumped into the area of LDAC systems due to its ability to utilise waste heat as its main driving energy. The LDAC system performs dehumidification by absorbing moisture from the surrounding air through the use of desiccants. As a result, energy savings of up to 50% can be enjoyed both domestically as well as industrially. A comparison between the various types of liquid desiccants in the market is made to determine the most suitable and efficient desiccant for the dehumidification process. Lithium chloride, despite its corrosive chemical properties, is the most commonly utilised desiccant in the LDAC system. Mixtures of desiccant solutions with similar reactivation temperatures are also getting relatively popular due their ability to resist crystallisation and low operating costs. Nevertheless, the implementation of plastic heat exchangers has allowed the LDAC system to overcome the corrosive properties of most desiccant salts. In this study, the overall flow distribution pattern of the new membrane is analyzed under three different input scenarios. The uniformity exhibited within these distribution flow patterns is critical in determining the operational parameters of the membrane. Experiments are also conducted to determine the overall dehumidification performance of the new membrane. Lithium chloride of different concentrations and input flow rates were utilized and the gathered information was computed in a psychometric chart. An industrial membrane produced by Memsys was utilised as a means of comparison throughout the span of two experiments.The results from the experiments showcased that the new membrane is best operated under the parameters of low flow rate and dual input port. Although the dehumidification prowess of the new design may not be as desirable as that of existing industrial grade membranes, it would certainly provide researchers in ERI@N the necessary groundwork for the next phase of research.